2014
DOI: 10.4047/jap.2014.6.1.8
|View full text |Cite|
|
Sign up to set email alerts
|

How will surface treatments affect the translucency of porcelain laminate veneers?

Abstract: PURPOSE. The purpose of this study was to evaluate whether surface treatments affect the translucency of laminate veneers with different shades and thicknesses. MATERIALS AND METHODS. A total of 224 disc-shaped ceramic veneers were prepared from A1, A3, HT (High Translucent) and HO (High Opaque) shades of IPS e.max Press (Ivoclar Vivadent) with 0.5 mm and 1.0 mm thicknesses. The ceramics were divided into four groups for surface treatments. Group C: no surface treatments; Group HF: etched with hydrofluoric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…In this study, all surface treatments significantly affected the translucency of resin‐based materials, whereas only airborne‐particle abrasion decreased the TP value of lithium disilicate ceramic. Consistent with the current study, Turgut et al also reported that lithium disilicate ceramic became more opaque after airborne‐particle abrasion, whereas HFA etching did not affect the translucency. In addition to the surface irregularities, kinetic energy transferred to the surface of the material during airborne‐particle abrasion with alumina particles, and heat increase during laser irradiation has been noted to cause melting of the materials’ surfaces .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, all surface treatments significantly affected the translucency of resin‐based materials, whereas only airborne‐particle abrasion decreased the TP value of lithium disilicate ceramic. Consistent with the current study, Turgut et al also reported that lithium disilicate ceramic became more opaque after airborne‐particle abrasion, whereas HFA etching did not affect the translucency. In addition to the surface irregularities, kinetic energy transferred to the surface of the material during airborne‐particle abrasion with alumina particles, and heat increase during laser irradiation has been noted to cause melting of the materials’ surfaces .…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of the microstructure of the restorative material, adhesive luting protocol requires conditioning of the intaglio surface of the restoration to enhance the bond strength of restorative material to resin cement. It has been reported that surface treatment affects not only bond strength but also mechanical and optical properties of ceramics . Therefore, this in vitro study investigated the effect of different surface treatment methods on the flexural strength, color, and translucency of current CAD/CAM restorative materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not use cores with different thicknesses because it was previously reported that the material thickness changes the translucency (4,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted on how translucency can affect the optical properties of all-ceramic systems (Akar et al, 2014;Al Ben Ali, Kang, Finkelman, Zandparsa, & Hirayama, 2014;Awad et al, 2015;Barizon et al, 2014;Harada et al, 2016;Heffernan et al, 2002;Johnston, 2014;Sen & Us, 2017;Skyllouriotis, Yamamoto, & Nathanson, 2017;Turgut et al, 2014;Vichi, Carrabba, Paravina, & Ferrari, 2014;Vichi et al, 2011;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%